An improved analytical method for mesh stiffness calculation of spur gears with tip relief - Ma, Hui; Zeng, Jin; Feng, Ranjiao; Pang, Xu; Wen, Bangchun (Mechanism and machine theory, 2016)
Due to the effects of gear flexibility, the extended tooth contact (ETC) can appear, which is the phenomenon that the incoming tooth pair gets into contact ahead of the theoretical start of contact and the outgoing tooth pair is out of contact later than the theoretical end of contact. A large calculation error for the time-varying mesh stiffness (TVMS) calculation can be caused if the effects of ETC are ignored, especially under the larger torques. In this paper, an improved analytical method (IAM) suitable for gear pairs with tip relief is established to determine time-varying mesh stiffness (TVMS), where the effects of ETC, nonlinear contact stiffness, revised fillet-foundation stiffness, and tooth profile modification are considered. Based on the improved analytical model, TVMS under different torques, lengths, and amounts of profile modification is compared with that obtained from analytical finite element approach [29] and from FE method. The results show that TVMS obtained from the IAM agrees well with that from FE method and from analytical FE approach [29], and the computational efficiency of the IAM is also much higher than that of FE method. •The revised analytic model considers the effect of extended tooth contact.•Fillet-foundation stiffness is revised in the new analytic model.•The revised model is also effective under tip relief.•The revise model is verified by finite element method.•The revise model is validated using FE-analytic approach.